2022
DOI: 10.1108/jrf-09-2021-0158
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the hedge and safe-haven properties of bond markets for cryptocurrency indices

Abstract: PurposeThis study quantified the hedge and safe haven features of bond markets for multiple cryptocurrency indices from June 2014 to April 2021 to highlight whether bond markets offer hedging facilities to uncertainty indices of cryptocurrencies.Design/methodology/approachThe authors employed the methodology of Baur and McDermott (2010) and AGDCC-GARCH model to measure the hedge and safe-haven characteristics of three bond markets (BBGT, SPGB and SKUK) for three uncertainty indexes of cryptocurrencies (UCRPR, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 116 publications
(33 citation statements)
references
References 48 publications
3
30
0
Order By: Relevance
“…On the whole, the results indicate that there exists a countercyclical relationship between business cycles and healthcare expenditure. In short, this means that the faster-emerging economies develop, the lower the healthcare expenditure will be (46). One possible explanation for this lies in the fact that during times of economic boom, there is an improvement in the overall living standards, therefore positively contributing to the health of the masses.…”
Section: Resultsmentioning
confidence: 99%
“…On the whole, the results indicate that there exists a countercyclical relationship between business cycles and healthcare expenditure. In short, this means that the faster-emerging economies develop, the lower the healthcare expenditure will be (46). One possible explanation for this lies in the fact that during times of economic boom, there is an improvement in the overall living standards, therefore positively contributing to the health of the masses.…”
Section: Resultsmentioning
confidence: 99%
“…The conclusions highlighted the positive impact of green financing on the profitability of wind energy projects. In a recent study, Karim et al (2022) underscored the importance of green finance and its impact on cryptocurrencies using an econometric model. They found that the GB market is a useful and safe financing tool in times of economic uncertainty.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, there are limited studies that have examined the above relationship. In addition, the studies have only explored the symmetric impact of cryptocurrencies on green bond markets [14,15]. The literature, on the other hand, suggests that the relationship between explanatory and outcome variables can be both symmetric and asymmetric [16].…”
Section: Introductionmentioning
confidence: 99%